Protein Misfolding, Aggregation and Conformational Diseases Part B: Molecular Mechanisms of Conformational Diseases - Uversky, Vladimir N.; Fink, Anthony; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Protein Misfolding, Aggregation and Conformational Diseases, Part B: Molecular Mechanisms of Conformational Diseases, is a comprehensive volume providing a broad and detailed discussion of the relationships of protein misfolding and aggregation with the pathogenesis of numerous conformational diseases. While the Part A was dedicated to the description of the general mechanisms underlying protein misfolding, aggregation, and development of protein deposition disorders, this volume summarizes recent achievements in the understanding of the molecular mechanisms of conformational diseases. Research indicates that these mechanisms are highly diverse and range from the altered protein structure leading to the enhanced propensity for aggregation/deposition or the impaired functions and ending with changes in supra-molecular structures or posttranslational modification. Protein Misfolding, Aggregation and Conformational Diseases, Part B: Molecular Mechanisms of Conformational Diseases, is an ideal book for pharmaceutical scientists, molecular and cellular biologists, biochemists, immunologists, protein scientists, and biophysicists.
Altered Protein Structure and Enhanced Aggregation/Deposition -- The Pathogenesis of Alzheimer’s Disease: General Overview -- Free Radicals, Metal Ions, and A? Aggregation and Neurotoxicity -- Progress in Understanding the Mechanisms of Neuronal Dysfunction and Degeneration in Parkinson’s Disease -- ?-Synuclein Aggregation and Parkinson’s Disease -- Cell Biology of ?-Synuclein: Implications in Parkinson’s Disease and Other Lewy Body Diseases -- Pathogenesis of Prion Diseases -- Mammalian Prion Protein -- The Yeast Prion Proteins Sup35p and Ure2p -- Immunoglobulin Light Chain and Systemic Light-Chain Amyloidosis -- Pancreatic Islet Amyloid and Diabetes -- ?2-Microglobulin and Dialysis-Related Amyloidosis -- Serum Amyloid A and AA Amyloidosis -- Point Mutations and Enhanced Protein Deposition -- Transthyretin and the Transthyretin Amyloidoses -- Human Lysozyme -- Serpins and the Diversity of Conformational Diseases -- Altered Protein Structure and Impaired Function -- Human Copper-Zinc Superoxide Dismutase and Familial Amyotrophic Lateral Sclerosis -- Understanding the Effects of Cancer-Associated Mutations in the Tumor Suppressor Protein p53: Structural Consequences of Mutations and Possible Ways of Rescuing Oncogenic Mutants -- Changes in Supramolecular Structure -- Protein Aggregation in Muscle Fibers and Respective Neuromuscular Disorders -- Muscular Dystrophies and Protein Mutations -- The Functional Consequences of Dystrophin Deficiency in Skeletal Muscles -- Eye Lens Proteins and Cataracts -- Altered Protein Structure and Changes in Cellular/Nuclear Function -- Glutamine/Asparagine-Rich Regions in Proteins and Polyglutamine Diseases -- Mechanistic Insights into the Polyglutamine Ataxias -- Molecular Pathogenesis of the Polyglutamine Disease: Spinal and Bulbar Muscular Atrophy -- Post-Translational Modification and Protein Conformational Diseases -- Protein Glycation and Cataract: A Conformational Disease -- Defective Glycosylation and Muscular Dystrophies.
Keywords: Immunology; Cell biology; Immunology; Cell Biology